2021
DOI: 10.36283/pjmd10-1/015
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering Activity as A Source of Life Satisfaction among Medical and Dental Students of Karachi, Pakistan

Abstract: Background: Community Service is an integral component of undergraduate medical education. A volunteer is an individual who, without pay, reaches out beyond the confines of their normal responsibilities; freely and willingly contribute in different ways. Volunteering and serving others can help decrease tension, mentally empower volunteers and offer purpose in life. This study aimed to assess the motivation behind volunteering activities among medical students. Methods: A cross sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…Our results indicated that 74.50% of our respondents had volunteered previously, which is higher than studies conducted in Japan (43%) [13], Pakistan (64%) [20], and even the previous study from Saudi Arabia (30.31%) [21] that investigated dental students. The reason for this difference could be due to our study including working dentists, who had a significantly higher percentage of previous volunteers than did the students.…”
Section: Plos Onecontrasting
confidence: 70%
See 3 more Smart Citations
“…Our results indicated that 74.50% of our respondents had volunteered previously, which is higher than studies conducted in Japan (43%) [13], Pakistan (64%) [20], and even the previous study from Saudi Arabia (30.31%) [21] that investigated dental students. The reason for this difference could be due to our study including working dentists, who had a significantly higher percentage of previous volunteers than did the students.…”
Section: Plos Onecontrasting
confidence: 70%
“…In fact, many volunteering studies have included dental students under the larger umbrella of other specialties, such as medicine and others, instead of investigating dental professionals in depth. These studies have shown the percentages of dental students in their studies who volunteered in Japan (43%) [ 13 ], Pakistan (64%) [ 20 ], and Saudi Arabia (30.31%) [ 21 ]. In addition, studies have shown high levels of interest and willingness to participate in volunteer activities among medical and dental students during disasters in Japan (89.9%) [ 13 ] and Nigeria (82.9%) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since most of the community programs were run and implemented by students themselves, they were able to nurture the desire to be involved and participate as opportunity arise. This is because volunteering can help reduce stress, mentally empower participants, and provide a sense of purpose in life (Emad et al, 2021), a phenomenon seen among medical students who can make a significant contribution to teaching and healthcare activities. Volunteering in healthcare is advantageous to medical students on both a personal and academic level.…”
Section: International Journal Of Research Studies In Education 55mentioning
confidence: 99%